Implementasi Algoritma Caesar Cipher untuk Enkripsi dan Dekripsi Pesan - Siti Fadiyah Nabila; Maisyarah Maisyarah; Zahara Vonna; Salsabila Arifa Hasibuan; Silfia Rahmadani Sitorus; Aninda Evioni; Ibnu Rusydi (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2026)
Information security is an essential aspect of digital communication, particularly in the exchange of text-based messages through open networks. Messages transmitted without protection are vulnerable to interception and unauthorized modification. One classical cryptographic technique that remains relevant as a foundational learning tool is the Caesar Cipher algorithm. This study aims to implement the Caesar Cipher algorithm for message encryption and decryption and to analyze its effectiveness and security level. The research method employed is a descriptive approach through literature review and a case study by applying character-shift techniques to text messages. The results indicate that the Caesar Cipher algorithm successfully transforms plaintext into ciphertext and restores it back to its original form through the decryption process. Although the algorithm is simple and easy to implement, it has significant limitations in terms of security due to its small key space and vulnerability to brute-force attacks. Therefore, Caesar Cipher is not suitable for protecting sensitive data but remains valuable as an introductory model for understanding basic cryptographic concepts.